2011
DOI: 10.1021/ac201408w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for Voltammetric Responses of Molecular-Solid Tetrathionaphthalene Confined on an Electrode

Abstract: The cyclic voltammetry (CV) of solid-state tetrathionaphthalene (TTN; particles with diameters from a few tens to hundreds of nanometers) confined on electrodes was analyzed quantitatively by considering the inert-zone potential, the thermodynamic and kinetic interactions, and the kinetics of the electrode reaction. Theoretical treatments are applied for clarifying the experimentally accessible corresponding parameters. From the potential of full peak width at half-height current (ΔE(p1/2)) and the peak curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…All solid-state ion-selective electrodes constructed with faradaic ion-to-electron transducing materials, such as poly­(3-octylthiophene) (POT), poly­(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole, 7,7,8,8-tetracyanoquinodimethane (TCQN), tetrathialfulvane (TFN), tetrathionaphtalene, or ferrocene (Fc), ,, have offered the possibility of controlling electrochemical reactions (i.e., oxidation of POT to POT + ) at the inner interface of the electrode, thereby triggering an ion transfer reaction across the membrane/sample interface.…”
mentioning
confidence: 99%
“…All solid-state ion-selective electrodes constructed with faradaic ion-to-electron transducing materials, such as poly­(3-octylthiophene) (POT), poly­(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole, 7,7,8,8-tetracyanoquinodimethane (TCQN), tetrathialfulvane (TFN), tetrathionaphtalene, or ferrocene (Fc), ,, have offered the possibility of controlling electrochemical reactions (i.e., oxidation of POT to POT + ) at the inner interface of the electrode, thereby triggering an ion transfer reaction across the membrane/sample interface.…”
mentioning
confidence: 99%
“…The corresponding potential, which has been called unusual quasi-reversibility (UQR) or apparent non-kinetic hysteresis in CV, is defined as a "N-shaped" free energy which is needed in the process being akin to a slow molecular relaxation, 13 or a phase-transition energy of a reactant layer during the charge neutralization process. 14 In the previous paper, 11 this potential is defined as the inert-zone potential, contribution of which is reduced as a constant potential value from the E p shift observed for the irreversible wave in calculation of the related kinetic parameters. Figure 2B exhibits the response for the charge-discharge curves for a laminated cell using LTO electrode.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent paper, 11 we have reported that the value of W can be evaluated from theoretical equations, which have been published by Laviron [15][16][17] in 1970 and later by Matsuda 12 in 1987, about the CV for the electro-active molecular confined on an electrode. Matsuda proposed the general equation (the eqn.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations